Lesser Himalayas to Qang Tang: A 500 Km Teleseismic Deployment to Test Geodynamic Models - Hirn, A.; Nercessian, A.; Sapin, M.; Lepine, J. C.; Sachpazi, M.; Ferrazzini, V.; Jiang, M.; Lu, Q. T.; Shi, D. N.; Ma, K.; et al. (Journal of Nepal Geological Society, 1995)
The deep structure across Himalayas-Tibet is resolved along a dense seismic array by the variation of arrival times, amplitudes, waveforms and polarizations of teleseismic body waves. The Himalayas rise over a strong increase in crustal thickness. Behind, although Tibet has the same elevation, the structure and physical state vary strongly in the Lhasa block. This is further North than continental subduction would have accumulated a cold root and further South than homogenous thickening would have resulted in wholesale delamination. Evidence for flow at depth in this system does not simply mirror the tectonic features of the brittle surface. Heterogeneity along, as well as across strike and with depth demands models other than steady-state two dimensional approximations in plane or section. Further data collecting experiments will be needed.